철전극 전기분해공정을 이용한 하수의 고도처리 연구 - 김민규(성수기공; 송영일; 이성기; 이용운; 최병순; 이윤희 (한국수처리학회지, 23(6), 2015)
This study was applied to advanced wastewater treatment process using the iron electrode in the electrolysis process, an electrode was provided a caterpillar type device in order to prevent contamination of the electrode. Research such as the removal rate was investigated in accordance with the current change and the electrode distance, the influent effective according to the seasonal variations. Results are as follows. Influent concentration was examined to be larger than the effect of the rainfall seasonal variations. Precipitation concentration is increased initially but gradually decreased. When the rain did not make indicate a higher concentration showed a regularly pattern. The higher the voltage has caused a high current, the electrode distance is 1.0 m occurred at a voltage higher than 0.7 m. Results BOD and T-N and given a change in the current corresponding to the electrode distance in the electrolytic process, effluent concentrations were lower when a higher current supply and near the electrode distance. BOD, COD, SS, T-N showed the highest removal rate in 20A, T-P investigation was high as in 10A. In this study, we determined that the most appropriate to use the plant 20A. The injection current 20A, regardless of the electrode distance BOD, COD, SS, TN, TP showed a high removal rate. In this study it was examined and found to comply with the organic matter decomposition and nitrogen and phosphorous removal process. KCI Citation Count: 0